Implementasi Kebijakan Pemberdayaan Lembaga Kemasyarakatan Dalam Pengelolaan Pembangunan Desa di Distrik Fakfak Kabupaten Fakfak Propinsi Papua Barat - Bame, Roberto; Posumah, Jhonny Hanny; Pangkey, Masje Silija (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : According to the mandate uu. No. 32 2004 that every village in the form of community instutions (LPM,PKK, and Others )which has the taks of as sisting the government of the village and is a partner inempowering communities to empower the village community institutions PP No. 72.2005 set clearly the position ofthe duties, functions and social institutions working relationship with the village government the aim of this study todetermine the extent of implementation of the policy of empowering the village community institutions in the districof fak – fak , fak-fak regeney.Results of the date analysis addressed ; (1) social institutions in villages, villages in the district have given fak– fak optimal role in the management of village government with establisment of the village ; (2) the development ofquality human resource administrators in social institutions did not optimal ; (3) the relationship work andcommunication between civil society and the government generally good village ; (4) the allocation of budgetaryfunds for the activities of social institutions ( LPM, PKK ) both of APB villages as well as from the budget still verryminimal.Based on the results of research in policy implementation deduced village empowerment of civil society in themanagemt of the distric rural development fak – fak is good enough but not optimalKeywords : Policy implementation, empowering the village community